Spontaneous intramural rupture of the oesophagus. Issue 8 (August 1990) - Steadman, C; Kerlin, P; Crimmins, F; Bell, J; Robinson, D; Dorrington, L; McIntyre, A
Abstract : The clinical, endoscopic, and radiological features of seven patients with an uncommon oesophageal injury characterised by long lacerations of the oesophageal mucosa with haematoma formation but without perforation are reported. The injuries were not related to forceful vomiting or any other definable cause but were similar to those previously described as intramural oesophageal rupture. Upper gastrointestinal endoscopy undertaken to identify the cause of haematemesis in six patients proved safe and useful. When dysphagia and odynophagia occurred early in the clinical course to alert the clinician to possible oesophageal injury, radiological contrast studies were used to exclude perforation. One patient in this study had oesophageal cavernocapillary haemangiomatosis which may have caused intramural oesophageal bleeding and submucosal dissection but in the remainder the aetiology of intramural oesophageal rupture remains uncertain. Conservative management was successful in all patients.